Peran layanan bimbingan konseling kampus dalam mencegah bunuh diri dikalangan mahasiswa - Mardianta, Nayya Hajar Bintang (Maliki Interdisciplinary Journal, 2024)
Suicide is a serious problem that affects individuals and can have a devastating impact on families and communities. Mental health is key in suicide prevention efforts. Guidance Counseling in higher education is really needed. Guidance counseling is a series of activities between counselors and clients face to face to help solve problems or simply provide criticism and suggestions. Guidance counseling can not only help students to be successful in the current era. However, counseling guidance must also be able to provide developmental services and prevent problems that could hinder the progress of studies. This article shows that counseling plays an important role in maintaining student mental health to reduce the death rate caused by suicide among students. Therefore, mental health has a big influence on student well-being.